Gamification in a News English Course - Yi-Chien Wang (MDPI AG, 2023)
Studies examining the link between gamification and News English learning are scant. This study explored the effects of a gamified learning activity using the card games, slides, and learning sheets (CSCL) model on News English learning performance through a quasi-experimental mixed-methods study design. Pretests and post-tests and students' self-reflections were employed to determine the students' learning performance and responses to the activity. Gamification significantly and positively affected the experimental group's (EG) News English learning performance, with the learning performance of both lower and higher achievers improving significantly. Furthermore, the EG participants regarded the activity to be a fun and interactive hands-on experience. Gamification was considered useful for content comprehension and vocabulary acquisition. The mechanisms through which the activity affected News English learning were analyzed, and implications for gamification application in News English and further research are presented.